QGIS and applications in territorial planning - Baghdadi, Nicolas, 1968-; Mallet, Clément; Zribi, Mehrez (QGIS in remote sensing set, 2018)
These four volumes present innovative thematic applications implemented using the open source software QGIS. These are applications that use remote sensing over continental surfaces. The volumes detail applications of remote sensing over continental surfaces, with a first one discussing applications for agriculture. A second one presents applications for forest, a third presents applications for the continental hydrology, and finally the last volume details applications for environment and risk issues.